EN FACE VERSUS 12-LINE RADIAL OPTICAL COHERENCE TOMOGRAPHY SCAN PATTERNS FOR DETECTION OF MACULAR FLUID IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue Volume 14:Issues 1(2020) (2020) - Adam, Murtaza K.; Shahlaee, Abtin; Samara, Wasim A.; Maguire, Joseph I.; Ho, Allen C.; Hsu, Jason
Abstract : Purpose: To compare fluid detection of autosegmented en face to 12-line radial spectral domain optical coherence tomography scan patterns in neovascular age-related macular degeneration. Methods: Retrospective observational case series. Sixty-seven patients (94 eyes) with neovascular age-related macular degeneration underwent autosegmented en face optical coherence tomography (with associated 304-line raster scan) and 12-line radial scan patterns. Sensitivity and specificity of fluid detection for en face scan and 12-line radial scans were determined by combining radial and 304-line raster scans as a gold standard. Results: Two hundred and fifty-eight en face and 12-line radial spectral domain optical coherence tomography scans were interpreted. Seventy-five scans (58.1%) had fluid, whereas 54 scans (41.9%) did not. En face scan pattern fluid detection sensitivity and specificity was 89.3% and 61.1%, respectively. Twelve-line radial scan pattern fluid detection sensitivity and specificity was 97.3% and 100%, respectively. The difference in fluid detection between scan patterns was statistically significant ( P = 0.01). Decreased central macular thickness was associated with false-positive ( P = 0.035) and false-negative ( P = 0.01) fluid detection on en face scans. Conclusion: En face optical coherence tomography alone is not as sensitive or specific as the 12-line radial scan pattern in detecting fluid in neovascular age-related macular degeneration. En face scans should be corroborated with other optical coherence tomography protocols to guide clinical decision making. Abstract : Supplemental Digital Content is Available in the Text.En face scans are less sensitive and specific than 12-line radial optical coherence tomography scans for detecting macular fluid in with neovascular age-related macular degeneration.